Identification of genetic loci for powdery mildew resistance in common wheat - Liu, Xia; Zhang, Xiaoqing; Meng, Xianghai; Liu, Peng; Lei, Menglin; Jin, Hui; Wang, Yanzhen; Jin, Yirong; Cui, Guoqing; Mu, Zhixin; Liu, Jindong; Jia, Xiaoyun (Frontiers in Plant Science, 2024)
Powdery mildew (PM) poses an extreme threat to wheat yields and quality. In this study, 262 recombinant inbred lines (RILs) of Doumai and Shi 4185 cross were used to mapping PM resistance genes across four environments. High-density genetic linkage map of the Doumai/Shi 4185RIL population was constructed using the wheat Illumina iSelect 90K single-nucleotide polymorphism (SNP) array. Totally, four stable QTLs for PM resistance, QPm.caas-2AS, QPm.caas-4AS, QPm.caas-4BL, and QPm.caas-6BS were detected and explain 5.6-15.6% of the phenotypic variances. Doumai contributed all the resistance alleles of QPm.caas-2AS, QPm.caas-4AS, QPm.caas-4BL, and QPm.caas-6BS. Among these, QPm.caas-4AS and QPm.caas-6BS overlapped with the previously reported loci, whereas QPm.caas-2AS and QPm.caas-4BL are potentially novel. In addition, six high-confidence genes encoding the NBS-LRR-like resistance protein, disease resistance protein family and calcium/calmodulin-dependent serine/threonine-kinase were selected as the candidate genes for PM resistance. Three kompetitive allele specific PCR (KASP) markers, Kasp_PMR_2AS for QPm.caas-2AS, Kasp_PMR_4BL for QPm.caas-4BL and Kasp_PMR_6BS for QPm.caas-6BS were developed and their genetic effects were validated in a natural population including 100 cultivars. These findings will offer valuable QTLs and available KASP markers to enhance wheat marker-assisted breeding for PM resistance.